Pemanfaatan Bahan Alami dalam Pewarnaan Kain untuk Pemberdayaan Ekonomi Kreatif Masyarakat Leuweung Tiis RW 01 - Ardhi Nurhuda; Bella Khoerunnisa Budiman; Diana Farid; Dini Zakiyyah Nur Insani; Fadel Adhi Alamsyach; Hani Haerunisa; Nabilah Luthfiyah Hasna; Nasywa Al’syifa Maulana; Nita Permata Sari; Syamil Ahmad Al Hijry; Zaki Mukhlis Abdilah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This Ecoprint Workshop aims to introduce the ecoprint technique to the Leuweung Tiis RW 01 community as one of the environmentally friendly methods in dyeing fabrics and opening up business opportunities for local communities through the creative economy. Ecoprint uses natural materials such as leaves, flowers, and other plant materials to produce unique motifs and colors. In this workshop, participants are taught how to utilize natural ingredients available in the surrounding environment to create products with high economic value. The results of this activity show that participants not only master the basic ecoprint techniques, but also understand the potential of ecoprint development as a promising business opportunity.